Factors affecting treatment outcomes in tuberculosis (TB) patients in the Limpopo Province, South Africa - Gafar, Mohammed Mergni (University of Limpopo (Turfloop Campus), 2013)
Tuberculosis (TB) threatens the public health all over the world. South Africa is ranked fifth on the list of 22 high burden countries. SA has not achieved the international targets for cure rate and default rate yet. This is attributed to high HIV/AIDS prevalence and emergence of multi- drug resistant TB. Limpopo Province experiences poor TB treatment outcome, in spite of the adoption of strategies that proved globally that they can improve the outcome. The factors affecting treatment outcome in Limpopo Province are as yet undocumented. The specific objectives of this study were to determine the demographic profile of TB patients in the Limpopo Province; to investigate the treatment outcomes and to establish the relationship between age, gender, HIV status, treatment regimen and health facility level and the treatment outcomes in patients diagnosed with pulmonaryTB for period between 2006- 2010, inclusive, in Limpopo Province. Method Retrospective data for the period between 2006 and 2010 (inclusive) were reviewed, and 1200 records of cases of confirmed TB patients were sampled from the ETR.net provincial database. All these patients were diagnosed and treated according to guidelines adopted by the national TB control programme. Standard WHO definitions were used to classify the TB treatment outcome. Chi squire test was used to investigate the association between age, gender, diagnostic category and treatment regimen and treatment outcome. Results Of the 1200 TB cases sampled, 656 (54%) were male. Most of them fell within the age group 22- 55 years (n=871; 72.5%)). According to diagnostic category, 1035 (86.2%) were new cases; 962 (80.1%) cases received regimen I (two months of rifampicin [R], isoniazid [H], pyrazinamide [Z} and ethambutol [E] followed by four months of rifampicin and isoniazid, 2RHZE+ 4RH); 893 (74.4%) cases had successful treatment; 118 (9.8%) defaulted on treatment; 26 (2.2%) had treatment failure, and 163 (13.6%) died. There was a strong association between age (P <0.001), diagnostic category (P < 0.001), treatment regimen (P < 0.001), and health facility level (P< 0.001) and treatment outcome. The success treatment was highly significant (P <0.001) for the cases that fell within the age group 3- 6 years, those that were diagnosed as new cases, those that received treatment at mine health facilities or were treated with regimen III (2RHZ + 4RH). While the default rate was highly significant (P< 0.05) for the cases aged 7- 12 or 22- 55 years, patients that had history of defaulting, and those that received treatment at a community health centre or village health facilities – treatment failure was highly significant (P< .05) for Those fell within age group 22-55 or 56- 74 years, those had initial treatment failure, those that received treatment at hospital or mobile health facilities or treated with regimen II (3RHZES + 5RH) while the death rate was highly significant (P< 0.05) for the cases either fall within age group 0-2, 22- 55 or 56- 74 years, had initial failure, received treatment at hospital or village health facilities or treated with regimen). The un success rate was very highly significant (P< 0.001) for those either characterized by; fall within age group 22- 55 years, had initial failure, received treatment at hospital or village health facilities or treated with regimen II. Conclusion TB treatment outcome are poor in the Limpopo Province, particularly among patients with previous history of TB treatment, those receiving treatment in hospitals, or those being treated with first line regimen II. This situation requires that the TB control programme and other relevant programmes be strengthened, for instance through integration at facility level, towards more effective response to the challenges which hamper progress towards international targets on TB. Further studies are needed to address the effect of HIV status and AIDS, CD4+ cell counts, anti-retroviral therapy (ART), cotrimoxazole preventive therapy (CPT) and radiological presentation, and their effect on TB treatment outcome in Limpopo Province. Those data are not routinely captured on ETR.net, hence were not included in the present study.
Thesis (M.Pharm.) --University of Limpopo, 2013
Keywords: Tuberculosis; Public health; HIV/AIDS; TB treatment; 616.9956825; Tubercolosis; Tubercolosis patients